International culinary influence on street food: an observatory study - Khairatun, Siti Nurhayati (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: This paper presents a street food profiling of one of the most popular tourist attractions in Melaka, Jonker Street. The main objective of this study is to develop a street food profile of Jonker Street in determining whether local or international culinary influence represents the food sold there. Research methodology: An on-site observation was conducted to investigate the types of food sold and the range of prices offered. A descriptive analysis was completed to characterize street food. Results: The findings indicated that most of the food sold here represents international and trendy flavor rather than local. Limitations: This study was self-funded and conducted on the Jonker Street location only. Due to that, no generalization can be derived from the data. Contribution: This study also provides a baseline reference for the tourism players in outlining strategies toward sustainable tourism relating to local culinary offerings. Keywords: Culinary tourism, Street food, Observatory study